A sensitive search for dark energy through chameleon scalar fields using neutron interferometry. (22nd January 2015) - Snow, W M; Arif, M; Heacock, B; Huber, M; Li, K; Pushin, D; Skavysh, V; Young, A R
Abstract: The physical origin of the dark energy, which is postulated to cause the accelerated expansion rate of the universe, is one of the major open questions of cosmology. A large subset of theories postulate the existence of a scalar field with a nonlinear coupling to matter chosen so that the effective range and/or strength of the field is greatly suppressed unless the source is placed in vacuum. We describe a measurement using neutron interferometry which can place a stringent upper bound on chameleon fields proposed as a solution to the problem of the origin of dark energy of the universe in the regime with a strongly-nolinear coupling term. In combination with other experiments searching for exotic short-range forces and laser-based measurements, slow neutron experiments are capable of eliminating this and many similar types of scalar-field-based dark energy models by laboratory experiments.